ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEMAMPUAN BERPIKIT KRITIS SISWA DALAM MENYELESAIKAN SOAL MATEMATIKA - Ni'mah, Uswatun; Ermawati, Diana; Amaliyah, Fitriyah (JURNAL MathEdu (Mathematic Education Journal), 2025)
The high and low levels of students' critical thinking abilities can be caused by the psychological development of each student. Critical thinking abilities can be influenced by internal factors such as physical condition, motivation, anxiety, habits and intellectual development. This research aims to analyze the factors that influence students' critical thinking abilities through mathematics problems. This research was conducted at SDN Ngemplak Kidul 03 Margoyoso, Pati. The method used in this research is qualitative with a case study approach. The subjects in this research consisted of 9 students, with three categories of critical thinking abilities, namely 3 subjects in the high category, 3 subjects in the medium category, and 3 subjects in the low category. The data collection techniques used were observations, interviews and documentation carried out on teachers and students. The results of the research show that 1) students in the category of high critical thinking abilities have good and positive physical condition, motivation, anxiety, habits and intellectual development. 2) students in the moderate critical thinking ability category have poor anxiety and motivation factors, but have good physical condition, habits and intellectual development factors. 3) students in the low critical thinking ability category have poor or negative physical conditions, motivation, anxiety, habits and intellectual development.